2009
DOI: 10.1126/science.1173651
|View full text |Cite
|
Sign up to set email alerts
|

An Invasive Plant Paradox

Abstract: This copy is for your personal, non-commercial use only.clicking here. colleagues, clients, or customers by , you can order high-quality copies for your If you wish to distribute this article to others here. following the guidelines can be obtained by Permission to republish or repurpose articles or portions of articles ): October 14, 2012 www.sciencemag.org (this information is current as ofThe following resources related to this article are available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
109
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 16 publications
(5 reference statements)
6
109
1
1
Order By: Relevance
“…Moreover, it has already infested large tracts of land in the industrial and residential areas. The same trend was reported in other countries by El-Keblawy and Al-Rawai [8] , Rout and Callaway [9] . ), Inderjit et al [10] .…”
Section: Introductionsupporting
confidence: 85%
“…Moreover, it has already infested large tracts of land in the industrial and residential areas. The same trend was reported in other countries by El-Keblawy and Al-Rawai [8] , Rout and Callaway [9] . ), Inderjit et al [10] .…”
Section: Introductionsupporting
confidence: 85%
“…Comparisons of invasives with conspecifics from their native range (Callaway et al 2004) or heterospecifics in the invaded range (Klironomos 2002) show that in general, invasive species experience positive plant-soil feedbacks or are simply less dependent on mutualists in the soil (Seifert et al 2009). In focusing our study on populations within the invaded range rather than on sampling the invasive range as a homogeneous entity, we have found that in contrast to earlier research and theoretical predictions (Rout and Callaway 2009), invasive populations may experience a range of feedbacks across their invaded range. Different feedbacks may result in varying rates of expansion for different populations.…”
Section: Plant-soil Feedbacksmentioning
confidence: 77%
“…Invasives often exude chemicals that disrupt symbioses between native plant species and beneficial microbes (Wardle et al 1994, Wolfe et al 2008 or otherwise alter the composition of soil microbial communities (Batten et al 2008). These distinctive invaded soils may affect the success of subsequent generations of plants growing at that site, creating a feedback loop in which soil conditions promoted by an invasive species promote further invasion (a positive plant-soil feedback; Klironomos 2002, Callaway et al 2004, Rout and Callaway 2009). Plant-soil feedbacks are abiotic or biotic soil-based mechanisms that account for shifts in plant population size and community composition (van der Putten et al 1993, Bever 1994.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to ecohydrology, woody species encroachment has been found to modify water distribution in soils through shifts in transpiration rates, more precipitation interception, and less water infiltration, potentially resulting in drier soils (Liao et al 2008, Rout and Callaway 2009, Boutton and Liao 2010, Awada et al 2013. These changes have negative impacts on grasses and resilience of the these ecosystems (Diez et al 2012).…”
Section: Introductionmentioning
confidence: 99%